Simplifying
12x + 10 + 3 + 8x = 0
Reorder the terms:
10 + 3 + 12x + 8x = 0
Combine like terms: 10 + 3 = 13
13 + 12x + 8x = 0
Combine like terms: 12x + 8x = 20x
13 + 20x = 0
Solving
13 + 20x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13' to each side of the equation.
13 + -13 + 20x = 0 + -13
Combine like terms: 13 + -13 = 0
0 + 20x = 0 + -13
20x = 0 + -13
Combine like terms: 0 + -13 = -13
20x = -13
Divide each side by '20'.
x = -0.65
Simplifying
x = -0.65
<h3>
Answer: 360</h3>
==========================================================
Explanation:
We have 3 even values (2,4, and 6) so this is the number of choices we have for the units digit. Recall that a number is even if the units digit is 0,2,4,6 or 8.
Once we have the units digit selected, we have 6-1 = 5 choices for the first slot, 6-2 = 4 choices for the second slot, and so on until we get down to 6-5 = 1 choice for the fifth slot
We could write it out like this
- slot one = 5 choices
- slot two = 4 choices
- slot three = 3 choices
- slot four = 2 choices
- slot five = 1 choice
- slot six = units digit = 3 choices
Multiply those values out: 5*4*3*2*1*3 = 360
There are 360 different even numbers possible.
Answer:
y = 2x - 3
Step-by-step explanation:
Start by writing out the given equation.
-2x + y = -3
The goal is to isolate the variable y.
For this equation, all you need to do is add 2x to each side.
-2x + y + 2x = -3 + 2x
Therefore, the answer is y = 2x -3.
I don't know if you are are familiar with the equation y = mx + b, but here's a little refresher. m is the slope, or in this case 2. b is the y-intercept, or in this case -3.
The equation y = mx + b is slope intercept form, so if you know this, you should be able to write any equation in slope intercept form.
Hope this helps!
Answer:do u mean divided 2?, then the answer is 325
Step-by-step explanation:650/2
Recall that the y-intercept is when the function passes the y-axis. This happens when x=0. Therefore, we can find our y-intercept by plugging x=0 into our function and solving for y.
6x + 9y = 18
6(0) + 9y = 18
0 + 9y = 18
9y = 18
y =2
Thus, our y-intercept is when x = 0 and y = 2, or (0,2).